IMPLEMENTASI PENENTUAN STRATEGI BERSAING DI TINJAU DARI ANALISIS SWOT DI PT. BANK SYARIAH INDONESIA (BSI) CABANG SAMBAS - Maskupah Maskupah (Cross-border, 2019)
Developments in Islamic banking continue to progress, but it should not make Islamic banks proud, because there are many things that must be addressed in Islamic banking. Bank Syariah Indonesia Branch Sambas. With this spin off process, Bank Syariah Indonesia Branch Sambas requires a strategy to compete with other Islamic banking. So to determine the strategy used, the researcher uses a SWOT analysis, namely analyzing internal and external factors at the Indonesian Sharia Bank Sambas Branch. The results of this study Internal factors in determining competitive strategy at Bank Syariah Indonesia Sambas Branch consist of strengths including:Good governance and behavior or culture of Islamic Banks, positive investment climate and high morale, normal FDR, positive contribution to society and environmental sustainability, helping entrepreneurs in the Sambas Region. And weaknesses include: Limited experts, lack of supporting facilities, lack of supporting regulations, promotion or introduction of door to door and technology that is still limited. External factors in determining competitive strategy at Bank Syariah Indonesia Sambas Branch consist of opportunities including: The majority of the Muslim community, cooperation, high community potential, MUI fatwa. And the threats include: Total share of banking, lack of understanding of Islamic banking, difficult and complicated impression on Islamic Banks, social impression on Islamic Banks and lack of support from the community. One of the strategies that can be used is to determine a competitive strategy at Bank Syariah Indonesia Sambas Branch, namely the stable grow strategy, meaning that in competition in Islamic banking